Mitochondria: the central hub linking exercise to enhanced cardiac function - Cai, Jiaqin; Wang, Tutu; Li, Shunchang (Frontiers in Physiology, 2026)
Sedentary lifestyle is a major risk factor for the occurrence and development of cardiovascular disease, which remains one of the leading contributors to global morbidity and mortality. Beyond inducing endothelial dysfunction, prolonged sedentary patterns trigger chronic inflammation and disrupt endogenous antioxidant defenses, resulting in mitochondrial dysfunction in cardiomyocytes and subsequent impairment of cardiac health. In contrast, regular physical exercise serves as an effective lifestyle intervention that mitigates sedentary-related cardiac damage and improves cardiac function. Mitochondria, as central organelles governing cellular survival and death, are thought to play a pivotal role in mediating the cardioprotective effects of exercise. However, the precise mitochondrial mechanisms underlying these benefits remain incompletely defined. This review aims to summarize current evidence on how exercise regulates mitochondrial function in the heart, with particular emphasis on recent advances linking mitochondrial respiration, dynamics, calcium homeostasis, inflammatory signaling, and oxidative stress to cardiac health. We further propose that exercise-induced improvements in mitochondrial function constitute a core mechanism underlying its cardioprotective effects. By comparing mitochondrial alterations under sedentary and exercise conditions, we provide a clearer mechanistic perspective on how lifestyle behaviors shape cardiac health. Furthermore, this paper also discusses signaling pathways that position mitochondria as key targets of exercise-induced cardiac protection.